A 1-Bit Coding Metasurface With Polarization Conversion in X-Band - Gao, Wen Hua; Chen, Mao; Cheng, Qiang; Cui, Tie Jun (Frontiers in Materials, 2022)
Polarization conversion metasurfaces are widely used in optical devices, microwave devices and communication systems, owing to their unique polarization modulation characteristics. However, in some applications (such as folded reflectarrays), the unit cell must be capable of polarization conversion and phase modulation. To the best of our knowledge, there are only a few related designs with both the functionalities. In this paper, we propose a well-performing 1-bit reconfigurable coding metasurface with polarization conversion. It realizes linear-to-linear polarization conversion in a 1.32 GHz bandwidth, and the conversion loss is within 1 dB. Simultaneously, the metasurface achieves a phase difference of approximately 180° by switching the working state of the PIN diodes. This metasurface has great potential for radar detection, folded reflectarrays, and other fields.